1987
DOI: 10.1172/jci112794
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of McArdle's disease (muscle glycogen phosphorylase deficiency). RNA and DNA analysis.

Abstract: Lack of muscle glycogen phosphorylase activity leads to McArdle's disease, a rare metabolic myopathy. To investigate its molecular basis at the nucleic acid level, we isolated muscle phosphorylase cDNA clones from a human cDNA library in Escherichia coli plasmid pBR 322. Subcloning of one insertion of M13 bacteriophage permitted its definite identification by sequencing. Northern blot experiments revealed one specific messenger RNA of 3.4 kilobases found uniquely in tissues expressing muscle phosphorylase.We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Total genomic DNA was isolated from tail biopsies as described (Davis et al, 1986). The presence of the transgene and copy number were evaluated as described by Southern (1975 with modifications as described (Gautron et al., 1987). Founder mice were crossed and analysis carried out on offspring, to avoid mosaicim and transgenes with multiple insertion sites, except for the ‐1,050‐intron founder mice, which were analyzed directly.…”
Section: Dna Constructsmentioning
confidence: 99%
“…Total genomic DNA was isolated from tail biopsies as described (Davis et al, 1986). The presence of the transgene and copy number were evaluated as described by Southern (1975 with modifications as described (Gautron et al., 1987). Founder mice were crossed and analysis carried out on offspring, to avoid mosaicim and transgenes with multiple insertion sites, except for the ‐1,050‐intron founder mice, which were analyzed directly.…”
Section: Dna Constructsmentioning
confidence: 99%
“…Slab gel IEF (as used in this study) offers clear advantages in both definition and separation over the assays used in the previous studies (36 (4,(39)(40)(41). A forthcoming report seems to indicate in many l * | patients the presence of a point mutation introducing a stop codon in the first exon of the gene (4 la).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies of myophosphorylase deficiency revealed that in most cases the protein is absent and the mRNA is missing or greatly reduced (4)(5)(6), in some patients there is a normal amount of either full-length or shorter mRNA, and in a few patients an inactive protein of normal or reduced size can be shown by immunoreaction with anti-M-GP antiserum (5)(6)(7)(8)(9). In human tissues there are three different isoforms ofglycogen phosphorylase (GP) ( 10), which are encoded by three separate genes (1 1-13).…”
Section: Introductionmentioning
confidence: 99%
“…It is exclusively caused by recessive variants in the PYGM gene, which codes for the skeletal muscle glycogen phosphorylase (myophosphorylase) enzyme [1,2]. The myophosphorylase enzyme is the first enzyme in the process to breakdown glycogen stores in skeletal muscle.…”
Section: Mutational Spectrummentioning
confidence: 99%